Fitzpatrick, Joann. North River. Photograph of people sitting around table eating. - Fitzpatrick, Joann
A photograph of 2 women and 4 men sitting around kitchen table eating buiscuits and drinking tea. Left to right: Walter Delaney, Michael Delaney, Josephine Stevens, Victor Stevens.